The use of critical thinking skills among university ESL students - Ismail, Mohd Rozaidi (Faculty of Communication and Modern Languages, Universiti Utara Malaysia, 2007)
This research was undertaken to measure the critical thinking ability of university ESL students and to determine the relationship between critical thinking ability and the (1) English language ability; (2) fields of study (or major); and (3) academic performance. The Cornell Critical Thinking Test Level X (CCTTX) developed by Ennis and Millman (1985) was used to determine the students’ critical thinking level and a questionnaire was administered to obtain other relevant data i.e. students’ English language ability, fields of study and academic performance. The respondents involved in the study were two hundred and sixty-one public university students in Pahang. The students’ CCTTX were marked and scores were given. Association between students’ critical thinking ability and English language ability, fields of study and academic performance were analysed via one-way analysis of variance using the Statistical Package for Social Sciences Version X (SPSS-X). The findings revealed that the overall scores obtained by the students in CCTTX test were low. There was a significant difference in the critical thinking scores with the students’ language ability. However, there were no significant differences recorded between the students’ CCTTX scores and their fields of study and academic performance. The implications of the findings for the English Language Curriculum were elaborated and relevant recommendations were made.